Temporal evolution of the key neurohumoral regulator renin in chronic stable HFrEF. (3rd October 2022) - Han, E; Prausmueller, S; Arfsten, H; Weidenhammer, A; Spinka, G; Bartko, P; Goliasch, G; Huelsmann, M; Pavo, N
Abstract: Background: Renin is the enzyme catalyzing the rate-limiting step of the Renin-Angiotensin-System (RAS) generating Angiotensin II (AngII). RAS inhibitors are a main pillar of current heart failure with reduced ejection fraction (HFrEF). Although used since over 30 years in clinical routine, the studied effects of RAS-inhibitors on renin level changes during the course of HFrEF and its impact on patient outcomes, especially under current guideline directed medical therapy (GDMT), are lacking. Methods: Consecutive patients with stable chronic HFrEF and GDMT were enrolled prospectively from the our outpatient unit of heart failure between 06/2013 and 08/2021. Active plasma renin concentration (ARC) was documented for all patients consecutively at first measurement, i.e. baseline (BL), and at follow-up (FUP) visits at 12, 24, 36, 48 and 60 months, respectively. BL renin was correlated with N-terminal pro B-type natriuretic peptide (NT-proBNP) and compared between NYHA class, HF medication use and renin levels between baseline and FUP timepoints. To assess the effect of changes in renin levels, patients were categorized into three groups based on the change of renin from baseline within the first year of observation: decrease = change >−50%, undulating=change between −50 to 50%, increase=change>50% and survival curves were displayed as Kaplan-Meier plots and compared for different ARC categories by the log-rank test. Results: A total of 491 patients were included in the study. BL characteristics are shown in Table1. Renin levels showed no relationship with HF severity reflected by a lack of correlation with NT-proBNP [rs=−0.05, p=0.273] and comparable levels between NYHA groups [p=0.753] (Figure 1A). Renin levels were further comparable for different RAS inhibitors and patients with and without beta blockers, however higher in patients with mineralocorticoid receptor antagonists (MRA) [189 μIE/ml vs. 59 μIE/ml, p=0.0001] and SGLT2-inhibitors [280 μIE/ml vs. 100 μIE/ml, p=0.004] (Figure 1B). Renin levels at different yearly FUP timepoints are displayed in Figure 1C. There was no significant difference in renin levels between BL and 1-year FUP, while renin concentration was increased at 2-year FUP [126 μIE/ml vs. 243 μIE/ml, p=0.002]. Baseline renin levels were not associated with survival [crude HR for an increase of 100μiE/ml 1.014 (95% CI: 0.997–1.032), p=0.102]. Within one year following BL, renin decreased in 77 (27.6%), was undulating in 74 (26.5%) and increased in 128 (45.9%) patients. Kaplan-Meier suggests worse survival for patients with increasing renin though the difference was statistically not significant [p=0.2573] (Figure 1D). Conclusion: Renin was elevated in patients with MRA and/or SGLT2-inhibitors. Renin tends to increase over time in stable HFrEF. Although RAS is the main target of HFrEF therapy, surprisingly there seems to be no strong association between RAS activation and thereby potential effectivity of achieved RAS-blockade and outcome. Funding Acknowledgement: Type of funding sources: None.